2018
DOI: 10.1111/ijd.14011
|View full text |Cite
|
Sign up to set email alerts
|

UVA‐1 phototherapy for the management of atopic dermatitis: a large retrospective study conducted in a low‐middle income country

Abstract: UVA-1 phototherapy can be an alternative for patients with severe atopic dermatitis even at lower doses than those described in other series (30 J/cm ) and not only for acute flares. Cumulative total dose is a variable that affects the clinical response directly. Large prospective studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…Las más recomendadas para dermatitis atópica son la RUV B de banda estrecha (UVB-NB) y la RUV-A1 (UVA1) (28)(36) (43). En general se recomienda el uso de UVB-NB para el manejo de lesiones crónicas mientras que de UVA1 para las lesiones agudas, aunque hay estudios que sugieren que UVA1 también genera buena respuesta en pacientes con lesiones crónicas (44).…”
Section: Fototerapiaunclassified
“…Las más recomendadas para dermatitis atópica son la RUV B de banda estrecha (UVB-NB) y la RUV-A1 (UVA1) (28)(36) (43). En general se recomienda el uso de UVB-NB para el manejo de lesiones crónicas mientras que de UVA1 para las lesiones agudas, aunque hay estudios que sugieren que UVA1 también genera buena respuesta en pacientes con lesiones crónicas (44).…”
Section: Fototerapiaunclassified
“…Regarding severe atopic dermatitis, the role of UVA1 phototherapy in treatment is well established [ 26 , 27 , 28 , 29 ]. A systematic review [ 30 ] of nine randomized trials found that, in adult patients with acute, severe atopic dermatitis, phototherapy with UVA1 was faster than that with conventional UVA/UVB in inducing clinical improvement, with a peak response after 10 treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet (UV) phototherapy has been recommended as a treatment option for AD cases that are refractory to basic care and topical therapies [ 104 , 118 ]. Importantly, UVA-1 and narrowband UVB (NB–UVB) are the most effective treatment modalities for improving clinical signs of AD [ 119 , 120 ]. Interestingly, low-dose UVB irradiation was reported to increase AMP expression and improve barrier recovery in the murine epidermis [ 121 ].…”
Section: Influence Of Ad Treatments On Ampsmentioning
confidence: 99%